The immune response to Covid-19 mRNA vaccination among Lymphoma patients receiving anti-CD20 treatment - Komlodi-Pasztor, Edina; Escarra-Senmarti, Marta; Bazer, Danielle A.; Bhatnagar, Aastha; Perez Heydrich, Carlos A.; Messmer, Marcus; Ambinder, Richard F.; Gladstone, Douglas E.; Clayton, Laura; Goodrich, Amy; Schoch, Laura; Wagner-Johnston, Nina; et al. (Frontiers in Immunology, 2024)
The monoclonal antibody rituximab improves clinical outcome in the treatment of CD20-positive lymphomatous neoplasms, and it is an established drug for treatment of these cancers. Successful mRNA COVID-19 (SARS-CoV-2) vaccination is extremely important for lymphoma patients because they tend to be elderly with comorbidities which leaves them at increased risk of poor outcomes once infected by Coronavirus. Anti-CD20 therapies such as rituximab, deplete B-cell populations and can affect vaccine efficacy. Therefore, a knowledge of the effect of the COVID-19 vaccination in this group is critical. We followed a cohort of 28 patients with CD20-positive lymphomatous malignancies treated with rituximab that started prior to their course of COVID-19 vaccination, including boosters. We assayed for vaccine “take” in the humoral (IgG and IgA) and cellular compartment. Here, we show that short-term and long-term development of IgG and IgA antibodies directed toward COVID-19 spike protein are reduced in these patients compared to healthy controls. Conversely, the robustness and breath of underlying T-cell response is equal to healthy controls. This response is not limited to specific parts of the spike protein but spans the spike region including response to the conserved Receptor Binding Domain (RBD). Our data informs on rational vaccine design and bodes well for future vaccination strategies that require strong induction of T-cell responses in these patients.